Effect of weight bearing on the joint angles of the fore- and hind limb of the dog - Watson, C.; Rochat, M.; Payton, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
In the dog the correct angles for arthrodesis of limb joints have been published in the veterinary literature. They can also be obtained by measuring the joint angles of the contralateral limb from a standing lateral radiograph. This study was undertaken to determine if increased weight-bearing had a significant effect on joint angles. Standing lateral radiographs of the foreand hind limbs were taken of dogs standing on all four legs and then with their contralateral limb elevated. A significant difference was found between the angles of the metacarpophalangeal and metatarsophalangeal joints (p ≤ 0.05) when the dog was bearing weight on all four limbs compared to when the contralateral limb was elevated. Significant differences were not found for the other joints that were evaluated (shoulder, elbow, antebrachial carpal, stifle tibiotarsal).
Keywords: Arthrodesis; weight bearing; joint angle